2003
DOI: 10.1007/s00284-002-3853-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Expression of Regulatory Locus sae in Staphylococcus aureus

Abstract: Global regulatory locus sae consists of a two-component signal transduction system coded by saeR and saeS genes that upregulates the transcription of several exoproteins. Northern analysis carried out in this study reveals the synthesis at late and post-exponential phases of a cotranscript of saeR and saeS structural genes of about 2.4 kb. This transcript is diminished in the isogenic agr:: tetM mutant. Likewise, transcriptional fusion experiments show that sae expression is downregulated in the agr null mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 20 publications
3
42
1
Order By: Relevance
“…SigB may act indirectly on sae expression due to SigB-dependent inhibition of the agr system (20). The agr-dependent P1 activation is consistent with previous results from others (12,33) emphasizing that within the regulatory cascade of virulence gene regulation, the sae system is placed as a central downstream regulator.…”
Section: Vol 190 2008supporting
confidence: 78%
“…SigB may act indirectly on sae expression due to SigB-dependent inhibition of the agr system (20). The agr-dependent P1 activation is consistent with previous results from others (12,33) emphasizing that within the regulatory cascade of virulence gene regulation, the sae system is placed as a central downstream regulator.…”
Section: Vol 190 2008supporting
confidence: 78%
“…For example, it has been reported that expression of the saeRS locus is activated by agr (Giraudo et al, 2003;Novick & Jiang, 2003). However, we did not observe a significant difference between the levels of saeRS expression between UAMS-1 and its agr mutant (Table 4).…”
Section: Transcriptional Profiling Of the Uams-1 Agr Reguloncontrasting
confidence: 49%
“…Evidence to support this hypothesis comes from the observation that L. reuteri RC-14 repressed the two-component signal-transduction system saeRS independently of agr. The saeRS system has been suggested to regulate the expression of many virulence factors downstream of agr, and to coordinate the agr quorum-sensing-dependent regulation with the effects of environmental signals (35)(36)(37). It has also been previously demonstrated in S. aureus Newman that saeRS is involved in the regulation of SSL11 expression (38), and that L. reuteri RC-14 inhibited SSL11 synthesis independently of the agr system (17).…”
Section: Discussionmentioning
confidence: 99%